Determinants of School Participation in Riau Province in 2019 - Abdul Aliem Siddique; Unggul Heriqbaldi (Trunojoyo University of Madura, 2021)
Education has an important role in economic development, not only in driving economic growth but also in breaking intergenerational poverty. For this reason, the Government of Indonesia has implemented a 12-year compulsory education program in the last decade. Through this program, it is hoped that school enrollment rates will increase and economic development will be of higher quality. However, the implementation of this program was not without obstacles. This study aims to analyze the determinants of school participation in Riau Province in 2019 using data from the National Socio-Economic Survey (SUSENAS). The results of this study indicate that the education of the head of the household, the level of welfare and gender have a significant effect on school participation of children aged 7-18 years.